Republic of Congo : 2001 Article IV. (IMF Staff Country Reports; Country Report ;, 2001)
The primary source of hyperinflation has been unbridled monetization of an uncontrolled budgetary deficit. The Central Bank of the Congo (BCC) has lost control of monetary policy, and its role has been reduced to financing the fiscal deficit. The IMF staff agrees with the government that achievement of the major targets requires a strong fiscal adjustment effort, a restrictive monetary policy, and a well-sequenced implementation of structural and sectoral reforms, together with the timely strengthening of administrative capacity with the help of the international community.